Plan de marketing turístico para la difusión de la gastronomía de la parroquia Malacatos- cantón Loja provincia de Loja. - JARAMILLO JARAMILLO, LUDI MAGALI (2013)
At present there is a strong need to promote culinary tourism in Ecuador, mainly because of the obvious potential for tourism that plays in the country and the desire to strengthen the economy of the same, looking for the source of alternatives for entrepreneurs and those who work in this area, showing increasing interest in working this resource. On the other hand, in terms of techniques and trade market, marketing plans have been taking space in the national and local levels long, for better or advance development of peoples, revealing that have influenced positively in all places applied for and secure the sale of products or services. Thanks to the study of gastronomy has failed to recognize many characteristic features of the site, knowing that the parish Malacatos represents an important place in the tourist environment, mainly for its pleasant climate, a fact that leads to visiting tourists. From this it aims to attract the tourist gaze to another sector of the parish Malacatos appealing as culinary art. On this basis, the objectives are established, the first is to make a diagnosis of the current situation of the cuisine of the parish, the second objective is to design marketing strategies for effective dissemination of gastronomy through an advertising video and a mini stand newsmagazine where gastronomy sector and the third goal is to socialize the marketing proposal to the authorities of the Autonomous Decentralized Malacatos Parish. To fulfill the three goals respectively used the following methods and techniques: the first objective analytical method was applied to understand behaviors and establish new theories, techniques attached with the interview and survey to collect data and establish percentages for the marketing plan, the second objective scientific method was used to learn the skills to implement the objective, accompanied by analytical method studied the local dishes, along with these documentary technique was used to collect and explain the gastronomy parish, and for the third objective took into account the descriptive method to give clear ideas to managers about the benefits of research and technology company in the sample is presented a schematic model for the improvement of the food in which relates to marketing. Within this thesis is information necessary for the development and support of the draft, as it includes important tools as; Porter Analysis and SWOT analysis, which we will meet existing errors allowed in the restaurant industry. After the completion of the surveys to ascertain the shortcomings that have the cuisine of the parish Malacatos, due to lack of promotion to attract more customers in this sector. We propose a solution to the problem identified, through the design of a promotional brochure culinary tour of the town, and, video advertising to promote the diffusion of the typical dishes of the sector, noting that this proposal will not only improve a a company, it will boost domestic tourism levels of the population, and not rather of Ecuador. As for the general results obtained, it is shown that the parish Malacatos cuisine is an important part of the culinary heritage of the region, but that unfortunately has a middling score in terms of quality concerns due to poor existing support on the issue training, which is creating a low range on offer for visitors. Highlights, the parish has gastronomic product Malacatos recognition as having a good track record that needs to be disseminated and promoted to be exalted in the way it deserves. Following the above, it is up to the authorities of the Autonomous Decentralized turn of the parish Malacatos implement this marketing plan, using the media to spread the tourist attractions and restaurants, the owners of the establishments organize and partnerships to achieve a consolidation and in administrative and operational staff of the establishments require their respective training. Finally, the entire investigative analysis helped to prioritize some conclusions: the culinary art of the town is very appreciated by the great flavor, but with strong quality and service deficiencies, we sought a proper disclosure of getting an outstanding gastronomy dissemination of plates desired by visitors.